The Influence of Service Quality and Customer Satisfaction on Customer Loyalty in Freight Forwarding Services of CV. Citra Surya Abadi Pontianak - Izham Al Qori; Samsuddin Samsuddin (SAINTIS Publishing, 2025)
This study aims to analyze the influence of service quality and customer satisfaction on customer loyalty in the freight forwarding services of CV. Citra Surya Abadi Pontianak. This research uses an associative quantitative approach with 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires, interviews, and field observations. The results of multiple regression analysis show the equation Y = 1.459 + 0.226X₁ + 0.425X₂ with a correlation coefficient (R) of 0.619, indicating that the relationship is in the strong category. The coefficient of determination (R²) of 38.3% indicates that customer loyalty is influenced by service quality and customer satisfaction by 38.3%, while the remaining 61.7% is influenced by other factors outside this study. The F test results show that service quality and customer satisfaction simultaneously have a positive and significant effect on customer loyalty. The partial t test results show that service quality and customer satisfaction each have a positive and significant effect on customer loyalty. In conclusion, service quality and customer satisfaction make a real contribution to increasing customer loyalty at CV. Citra Surya Abadi Pontianak. This study recommends the need for continuous improvement of service quality and customer satisfaction to maintain loyalty. Future research is expected to add other variables so that the results are more comprehensive.